THE INFLUENCE OF CHARGE DENSITY ON THE INTERACTION BETWEEN SODIUM NDUDECYL SULPHATE (SDS) WITH H1 (Journal of Sciences, Islamic Republic of Iran)
The binding data for the interaction of SDS with HI, in aqueous solution at various ionic strengths have been measured by equlibrium dialysis, and investigated spectroscapicaliy. The effect of charge density on the interaction is shown to be of considerable interest. The presence of NaCl causes conformational changes on the structure of HI; whereas this phenomena seems to become more intensified upon contact with SDS. The existence and the importance of charge density which cause additional forces in the macromolecular structures at identical ionic strengths is reported